Pengaruh Kepemimpinan Kenabian dan Iklim Organisasi terhadap Komitmen Organisasi pada Pengurus LDK Al-Ihsan UIN Antasari Banjarmasin - Nisa, Khairun; Musfichin, Musfichin; Komalasari, Shanty (Islamic Psychology Study Program, Faculty of Ushluddin and Humanities, UIN Antasari Banj, 2021)
Organizational commitment is a desire that a person has to stay afloat and involve himself in every organized activity. Organizational commitment appears in a person due to emotional ties and moral support both to fellow members of the organization and to leaders and members. Basically, people who have good organizational commitment will have these aspects in themselves, namely identification, loyalty, and involvement. So in this case, the researcher wants to do research on the Influence of Prophetic Leadership and Organizational Climate on Organizational Commitment in Al Ihsan LDK Management UIN Antasari Banjarmasin. This research is a quantitative research with associative research type. The population in this study were 51 administrators of LDK Al Ihsan UIN Antasari Banjarmasin. The results of this study are: 1) There is a significant influence between prophetic leadership on organizational commitment to the board of SDK Al Ihsan UIN Antasari Banjarmasin with a significance level of 0.018 (p <0.05) with an effective contribution of 10.9%. 2) There is a significant influence between organizational climate on organizational commitment to the management of SDK Al Ihsan UIN Antasari Banjarmasin with a significance level of 0.000 (p <0.05) with an effective contribution of 48.0%. 3) There is a significant influence between prophetic leadership and organizational climate on organizational commitment to the management of LDK Al Ihsan UIN Antasari Banjarmasin with a significance level of 0.000 (p <0.05) and together provide an effective contribution of 53.7%.